Assistance in designing STEM-based learning at the Muhammadiyah 1 Paiton research-based elementary school - Ahmad Fauzi; Fuad Jaya Miharja; Muthia Maharani Syaiful; Putri Nurul Nabilah; Nafisah Nur Azizah; Nifi Maulidyah; Salsabiilaa Roihanah (Universitas Muhammadiyah Malang, 2023)
STEM learning has now become the main approach applied in various schools in many countries. One of the obstacles faced by various schools in Indonesia in implementing STEM is the lack of understanding and experience of teachers about STEM-based learning. The purpose of this service program was to assist SD Muhammadiyah 1 Paiton Probolinggo in preparing and implementing STEM learning. The solution to the problems offered is socialization and assistance in designing STEM learning. The order of these community service activities was: 1) Matching Perceptions between the Community Service Team and Partner Schools; 2) Presentation of Series 1 Material: Innovative and STEM Learning Models; 3) Presentation of Series 2 Material: Lesson Study and Learning Community; and 4) STEM learning workshops. After carrying out community service activities at SD Muhammadiyah 1 Paiton, there has been a significant and large increase in teacher knowledge regarding STEM learning from before (M = 63.3, SD = 14.9) to after the service program (M = 95.6, SD = 6), t(11) = 6.6, p < .001, d = 1.91. Even though this service program has shown satisfactory results, this program needs to continue so that the learning community of teachers who able to optimize the design so that the implementation of STEM learning can be realized optimally.